Exploring the impact of PEGylation on pharmacokinetics: a size-dependent effect of polyethylene glycol on prostate-specific membrane antigen inhibitors - Yang Liu; Li Xia; Haiyang Li; Ping Cai; Sufan Tang; Yue Feng; Guangfu Liu; Yue Chen; Nan Liu; Wei Zhang; Zhijun Zhou (EJNMMI Research, 2024)
Abstract Background Prostate cancer is the second most frequent cancer and the fifth leading cause of cancer-related deaths in men. Prostate-specific membrane antigen (PSMA) as a target has gained increasing attention. This research aims to investigate and understand how altering size of PEG impacts the in vitro and in vivo behavior and performance of PSMA inhibitors, with a specific focus on their pharmacokinetic characteristics and targeting properties. Results Two 68Ga-labeled PSMA-targeted radiotracers were developed, namely [68Ga]Ga-PP4-WD and [68Ga]Ga-PP8-WD, with varying sizes of polyethylene glycol (PEG). [68Ga]Ga-PP4-WD and [68Ga]Ga-PP8-WD had excellent affinity for PSMA with IC50 being 8.06 ± 0.91, 6.13 ± 0.79 nM, respectively. Both tracers enabled clear visualization of LNCaP tumors in PET images with excellent tumor-to-background contrast. They also revealed highly efficient uptake and internalization into LNCaP cells, increasing over time. The biodistribution studies demonstrated that both radioligands exhibited significant and specific uptake into LNCaP tumors. Furthermore, they were rapidly cleared through the renal pathway, as evidenced by [68Ga]Ga-PP4-WD and [68Ga]Ga-PP8-WD showing a tenfold and a fivefold less in renal uptake, respectively, compared to [68Ga]Ga-Flu-1 in 30 min. Both in vitro and in vivo experiments demonstrated that PEG size significantly impacted tumor-targeting and pharmacokinetic properties. Conclusions These radiotracers have demonstrated their effectiveness in significantly reducing kidney uptake while maintaining the absorbed dose in tumors. Both radiotracers exhibited strong binding and internalization characteristics in vitro, displayed high specificity and affinity for PSMA in vivo.